Prevalência de Dismenorreia em mulheres brasileiras - Bernardino, Mariana Lara (Universidade Federal de São Carlos, 2020)
Introduction: Dysmenorrhea is a chronic pain syndrome characterized by pelvic or abdominal pain associated with menstrual period and menstruation. Objective: To analyze the prevalence of dysmenorrhea in Brazilian women. Methods: Preparation of a questionnaire containing 38 questions and a final where participants could leave questions or suggestions. This questionnaire was placed on an online platform and disseminated through social media. Women who were in the period between menacme and menopause and who had menstruated in the last three months were included. Results: The sample of 10,070 women found that 81.7% of them were aged between 18 and 30 years. The prevalence of dysmenorrhea in the last month was 90.7%, with mild (29.1%), moderate (40.4%) and severe (21.2%) pain. Conclusion: Dysmenorrhea had a high prevalence in the group of women studied, higher than in studies carried out in other countries. Even with a predominance in the Southeast region, this study managed to cover women from all regions of Brazil.
Prevalence of Dysmenorrhea in Brazilian Women
Keywords: Dismenorreia; Estudo de Prevalência; Questionário; CIENCIAS DA SAUDE::MEDICINA::SAUDE MATERNO-INFANTIL